Ursodeoxycholic acid alleviates high-fat diet-induced liver injury by modulating gut microbiota-mediated bile acid metabolism: an integrated microbiota-metabolomics analysis - Dong, Xueyun; Sun, Wen; Xu, Hao; Xie, Yunhan; He, Jiayuan; Liu, Xuehui; Liu, Xinyu; Ali, Asmaa; Chen, Min; Zhang, Leilei; Wu, Liang; Shao, Keke (Frontiers in Nutrition, 2026)
PurposeUrsodeoxycholic acid (UDCA), a naturally occurring bile acid with established hepatoprotective properties, has garnered attention for its potential role in metabolic health. This study provides scientific validation for these traditional uses by demonstrating UDCA’s protective mechanisms against non-alcoholic fatty liver disease (NAFLD) through gut microbiota modulation and metabolic regulation. This study elucidates the therapeutic mechanisms of UDCA against high-fat diet-induced NAFLD through integrated microbiota-metabolomics analysis.MethodsUsing a 12-week murine NAFLD model, oral UDCA (15 mg/kg/day and 30 mg/kg/day) was administered to evaluate its hepatoprotective effects. Hepatic steatosis and injury were assessed via serum ALT/AST levels, lipid profiles, and histopathology. Ultra-performance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS) quantified bile acid metabolites, while 16S rRNA sequencing analyzed gut microbiota composition. Serum metabolomics and network pharmacology were employed to identify metabolic pathways and mechanistic targets, respectively. Molecular analyses (qPCR/Western blot) assessed PPARγ/Nrf2/NF-κB signaling.ResultsUDCA treatment significantly ameliorated high-fat diet-induced NAFLD, as demonstrated by improved serum ALT/AST levels, attenuated hepatic steatosis, and reduced histopathological damage. UPLC-MS/MS analysis revealed a marked reorganization of bile acid metabolism, characterized by elevated non-12α-hydroxylated bile acids (UDCA, TUDCA) and enhanced alternative synthesis via CYP27A1 upregulation. 16S rRNA sequencing identified UDCA-driven restructuring of the gut microbiota, with specific enrichment of short-chain fatty acid-producing Muribaculum spp. and suppression of pro-inflammatory Prevotella (CAG-485). Serum metabolomics further confirmed these benefits, showing increased eicosapentaenoic acid (anti-inflammatory) and decreased long-chain acylcarnitines (lipid peroxidation markers). At the molecular level, UDCA activated PPARγ/Nrf2 antioxidative signaling while inhibiting NF-κB-mediated inflammation, and network pharmacology analysis identified 225 potential targets (including TNF-α, IL6, and NF-κB) within lipid/atherosclerosis pathways, collectively underscoring UDCA’s multimodal protective mechanisms against NAFLD.ConclusionThese findings validate UDCA’s multifaceted hepatoprotection via microbiota-bile acid crosstalk and metabolic-inflammatory modulation. The study provides a mechanistic basis for UDCA’s traditional use in hepatobiliary disorders by integrating microbial, metabolic, and molecular evidence.